Stress and immune response to bacterial LPS in the sea urchin Paracentrotus lividus (Lamarck, 1816). Issue 92 (September 2019) - Chiaramonte, Marco; Inguglia, Luigi; Vazzana, Mirella; Deidun, Alan; Arizza, Vincenzo
Abstract: The immune system of the sea urchin species Paracentrotus lividus is highly complex and, as yet, poorly understood. P. lividus coelomocytes mediate immune response through phagocytosis and encapsulation of non-self particles, in addition to the production of antimicrobial molecules. Despite this understanding, details of exactly how these processes occur and the mechanisms which drive them are still in need of clarification. In this study, we show how the bacterial lipopolysaccharides (LPS) is able to induce a stress response which increases the levels of the heat shock proteins HSP70 and HSP90 only a few hours after treatment. This study also shows that LPS treatment increases the expression of the β-thymosin-derivated protein paracentrin, the precursor of antimicrobial peptides. Highlights: Immune response in Paracentrotus lividus after stimulation with LPS. Echinoderm immune response and HSP90 and HSP70 expression. β-Thymosin modulation following LPS treatment.